1994
DOI: 10.1007/bf03009831
|View full text |Cite
|
Sign up to set email alerts
|

Hydromorphone patient-controlled analgesia (PCA) after coronary artery bypass surgery

Abstract: We conducted a study to compare the effectiveness of patientcontrolled analgesia (PCA) technique to conventional analgesic therapy (CAT) after coronary artery bypass graft (CABG). The PCA group received hydromorphone 0.1 mg" hr -t basal infusion and bolus doses of 0.2 mg Q 5 min (maximum L2 mg" hr -j)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…In another study of PCA with morphine and hydromorphone, doses and analgesia were similar [85]. A double-blind, randomized, controlled trial of 72 patients showed that PCA with hydromorphone achieves slightly better postoperative pain relief, and minimal side-effects and sedation in cardiac surgery compared with conventional analgesic therapy [96].…”
Section: Painmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study of PCA with morphine and hydromorphone, doses and analgesia were similar [85]. A double-blind, randomized, controlled trial of 72 patients showed that PCA with hydromorphone achieves slightly better postoperative pain relief, and minimal side-effects and sedation in cardiac surgery compared with conventional analgesic therapy [96].…”
Section: Painmentioning
confidence: 97%
“…Drowsiness and cognitive dysfunction are reported side-effects of all opioids [7,47,69,87,96]. They occur in up to 23% of patients treated with i.v.…”
Section: Sedationmentioning
confidence: 99%
“…Opioids have been used in intravenous, patient-controlled analgesia after coronary bypass surgery (15), subcutaneous infusion (13,16) and oral administration (17) in patients suffering from severe pain due to malignant disease. In patients with unacceptable side effects of morphine, such as hyperalgesia and myoclonus (3), hydromorphone may be a beneficial alternative.…”
mentioning
confidence: 99%
“…9) In previous researches, it had been shown that patients in PCA group after CABG procedures had more rapidly decreasing VAS scores than those in conventional analgesia group. 15) The authors had also advocated that VAS scores were lower in the former group at the time of extubation and on 3rd postoperative day, and thus lower incidences of myocardial ischemia were found. 15) In the present study, continuous infusion and PCA administration methods were used on patients that have undergone sternotomy in widely accepted dosing regimens.…”
Section: Discussionmentioning
confidence: 99%
“…15) The authors had also advocated that VAS scores were lower in the former group at the time of extubation and on 3rd postoperative day, and thus lower incidences of myocardial ischemia were found. 15) In the present study, continuous infusion and PCA administration methods were used on patients that have undergone sternotomy in widely accepted dosing regimens. In addition to continuous infusion, approximately 12 times of bolus doses of the analgesics had to be used in all 4 groups except the meperidine group.…”
Section: Discussionmentioning
confidence: 99%